Bisnis Website di Era Digital: Analisis Tantangan dan Peluang Pada Usaha Fastdigital - Muhamad Makhfud Fakhrudin; Purwanto Purwanto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
In the digital era, business is growing rapidly, especially in the context of website business. This article analyses the challenges and opportunities faced by FastDigitale Enterprises, a start-up in the website building business. The main challenges include cybersecurity, data privacy, fierce competition, rapid technological trends, dependence on technology, lack of digital skills, cost of implementing technology, customer acceptance, customer trust, legal compliance, scalability, changing consumer behavior, and limited resources. On the other hand, opportunities involve website creation for local businesses, e-commerce solutions, personal portfolios & blogs, web application development, mobile responsive websites, digital consulting services, and security & secure web development. With a holistic approach, this article details strategies to overcome challenges and Capitalism on opportunities, guiding FastDigitale to success in the digital age.